Analysis of Auditors' Perceptions of Artificial Intelligence on the Audit Process - Nurfaizi, M Fadilah; Hasnawati, Hasnawati (Syntax Corporation, 2024)
This research aims to determine the influence of Perceived Easy of Use Assisted System, Perceived Easy of Use Augmented System, Perceived Usefulness Assisted System, and Perceived Usefulness Augmented System on the Audit Process. This research uses primary data obtained from questionnaire data distributed to accountants who work in public accounting firms in Indonesia. The sampling technique used was purposive sampling with multiple regression analysis method. The analytical tool used in this research is SPSS 27.0. The results of research using multiple data regression analysis show (1) Perceived Easy of Use Assisted System has an effect on the Audit Process (2) Perceived Easy of Use Augmented System has no effect on the Audit Process (3) Perceived Usefulness of the Assisted System has no effect on the Audit Process (4 ) Perceived Usefulness of the Augmented System has no effect on the Audit Process.